Prolonged immigration detention, complicity and boycotts - Jansen, Melanie (Journal of medical ethics, 2018)
Australia’s punitive policy towards people seeking asylum deliberately causes severe psychological harm and meets recognised definitions of torture. Consequently, there is a tension between doctors’ obligation not to be complicit in torture and doctors’ obligation to provide best possible care to their patients, including those seeking asylum. In this paper, we explore the nature of complicity and discuss the arguments for and against a proposed call for doctors to boycott working in immigration detention. We conclude that a degree of complicity is unavoidable when working in immigration detention, but that it may be ethically justifiable. We identify ways to minimise the harms associated with complicity and argue that it is ethical to continue working in immigration detention as long as due care and attention is paid to minimising the harms of complicity.